Daily feeding frequency impacts muscle characteristics and fat deposition in finishing pigs associated with alterations in microbiota composition and bile acid profile - Hu, Luga; Tang, Huayu; Xie, Zhaoxi; Yi, Hongyu; Feng, Lunjie; Zhou, Pan; Zhang, Yong; Liu, Jingbo; Ao, Xiang; Zhou, Jianchuan; Yan, Honglin (Frontiers in Microbiology, 2025)
IntroductionFeeding frequency has been shown to affect growth and body composition of the host associated with gut microbiota. It remains unknown whether adjusting feeding frequency could effectively regulate both skeletal muscle development and whole-body lipid metabolism and thus affect carcass composition and feed conversion efficiency. Therefore, this study aimed to explore the effects of feeding frequency on muscle growth, fat deposition, cecal microbiota composition, and bile acid composition in finishing pigs.MethodsSixteen Sichuan-Tibetan black pigs, with an initial weight of 121.50 ± 1.60 kg, were divided into two groups and fed either two meals (M2) or four meals (M4) per day. The trial lasted 30 days. The muscle fiber characteristics, lipid metabolism in adipose tissue, and cecal microbiota and bile acid composition were determined.ResultsThe present study revealed that pigs fed four meals exhibited a lower feed-to-gain ratio, abdominal fat weight, and average backfat thickness (p < 0.05), as well as a higher loin eye area (p = 0.09) and myofiber diameter in the longissimus muscle than their counterparts. The mRNA expression of slow-twitch fiber and myogenesis-associated genes in the longissimus muscle was upregulated, while lipid metabolism-related genes in the backfat were downregulated in the M4 group compared to the M2 group (p < 0.05). The M4 pigs exhibited higher abundances of Firmicutes, Actinobacteriota, Bacillus, Clostridium_sensu_1, and Romboutsia, and lower abundances of Spirochaetota, Verrucomicrobiota, Treponema, and Muribaculaceae in the cecal content than the M2 pigs (p < 0.05). A higher feeding frequency increased the levels of primary bile acids and decreased the concentrations of taurine-conjugated bile acids in the cecal content of pigs (p < 0.05).ConclusionOur research suggested that the M4 feeding pattern, compared to the M2 pattern, promoted muscle growth and reduced fat deposition by enhancing fast- to slow-twitch fiber conversion and myogenesis in the muscle and repressing lipid metabolism in adipose tissue, associated with altered microbiota composition and bile acid profiles.